Desempenho de linhas de transmissão EAT e UAT frente a descargas atmosféricas: Influência da ruptura em meio vão - Leonardo de Carvalho Rocha (2009)
Lightning is the main source of transmission lines outages. Thus, it is necessary the full understanding of the main mechanisms related to outages due to lightning incidences. This work emphasizes the lightning performance of lines with nominal voltage levels above 230 kV.This thesis presents a specific analysis of the main characteristics associated to outages caused by shielding failure and midspan backflashover, which are mechanisms that influence significantly the outage rates of transmission lines with nominal voltage levels above 230 kV. The comprehension of those mechanisms may provide technical support to the design of actions related to the line protection, inorder to improve their lightning performance, decreasing the failure probability. In order to discuss the shielding failure influence on the lightning performance, an elementary description of the phenomenon is presented. The basic concepts regarding to the traditional methodology of electrogeometric model used for shielding failure calculations and the main challenges in the computation of failure rates are considered, based on recent works dedicated to the theme. Regarding the midspan backflashover, this work discusses the main aspects relatedto the phenomenon, the mechanisms involved in the establishment of the resultant overvoltages at the stricken point and the respective parameters that influence their magnitude. The midspan backflashover phenomenon is simulated from the modeling of two geometrical configurations of 500 kV transmission lines and considering both the first- and subsequent-stroke current waveforms. From the resultant overvoltages, the midspan backflashover rates are estimated for each line configuration.